Implementation Of Digital Marketing At Jerry Me & Nails - Hanita Bina; Golan Hasan (ConCEPt - Conference on Community Engagement Project, 2023)
The era of the Covid-19 pandemic throughout the world is in the midst of recovery, including Indonesia. Because it causes most of the daily activities to be replaced by the online system. This has caused some MSMEs to implement business marketing through digital systems.This research aims to create and implement the best business strategy in this current digital era for Jerry Me & Nails, which is located in Batam, Indonesia. This business strategy is to scan barcode to visit existing social media pages, one of them is Instagram as a social media platform. Not only that, we have interesting events, one of which is holding a promotion for the 13th anniversary celebration by making digital posters with attractive prizes within the specified time.The project started in September 2022 and was carried out until November 2022. The strategy that will be used in promoting Jerry Me & Nails is digital-based advertising. The implementation of this marketing strategy is expected to increase sales of Jerry Me & Nails